Laser lithotripsy of difficult bile duct stones under direct visual control. Issue 3 (March 1993) - Neuhaus, H; Hoffmann, W; Zillinger, C; Classen, M
Abstract : Biliary laser lithotripsy was performed under direct visual control in 35 consecutive patients not amenable to routine endoscopy. The patients had 1-50 (median 1) bile duct stones with the greatest diameter of the largest stone being 9-42 mm (median 20 mm). Conventional endoscopic treatment had failed because of an inaccessible papilla (16 patients), biliary strictures (seven patients), and impaction or large size of calculi (12 patients). Twelve patients, depending on their anatomical condition, underwent peroral cholangioscopy by means of a mother-babyscope system. Percutaneous cholangioscopy was initially carried out in 23 patients, 7-20 days (median 10 days) after creation of a transhepatic fistula. Pulsed dye laser (32 patients) or alexandrite laser (three patients) lithotripsy was applied under an appropriate direct visual control in all cases. Complete stone disintegration succeeded in 33 of 35 patients. All resultant fragments passed the papilla within a mean number of 1.3 treatment sessions. Peroral cholangioscopic lithotripsy failed in two cases. One patient successfully underwent percutaneous laser treatment and the other patient was referred to surgery. Fever, temporary haemobilia, or a subcapsular liver haematoma were seen in a total of eight patients during establishment of the cutaneobiliary fistula. A 95 year old patient who had been admitted with septic cholangitis died because of cardiorespiratory failure 5 days after bile duct clearance. It is concluded that laser lithotripsy performed under a direct visual control is an effective and safe procedure for the non-surgical treatment of difficult bile duct stones. Ductal clearance can usually be achieved in a single treatment session when the papilla and the stones are accessible by the peroral route. Percutaneous cholangioscopic lithotripsy is more time consuming but highly effective even in patients with a difficult anatomy, bile duct strictures, or intrahepatic calculi. This approach should be limited, however, to cases not amenable to retrograde procedures because the creation of the cutaneobiliary fistula is not without risks.